Management of pediatric refractory epilepsy - Anyanwu, Chinekwu; Motamedi, Gholam K. (Journal of Pediatric Epilepsy, 2012)
About half of patients with epilepsy will become seizure free upon treatment with the first antiepileptic drug (AED). After trying further medications, overall, two thirds of patients will become seizure free on AED(s), while the remaining one third will continue having seizures. Patients who have failed treatment with adequate trials of two appropriate and tolerated AEDs, whether as monotherapy or in combination, are considered refractory (drug resistant). Appropriate diagnosis and optimal control of seizures are essential for a successful treatment and improved quality of life of patients with epilepsy. Since the introduction of a number of newer AEDs in the last decade, there have been improvements in tolerability and side effect profile of AED therapy. Failure to respond to the initial pharmacologic treatment should prompt trials of alternative options including reevaluation for accurate diagnosis and optimizing AED therapy, epilepsy (resective) surgery, vagus nerve stimulation, ketogenic diet, and a series of potentially effective pharmacological and surgical treatments currently under investigation.
Keywords: Pediatric refractory epilepsy; drug resistant epilepsy; pharmacotherapy